TURKISH COMMUNITY IN GERMANY AND THE ROLE OF TURKISH COMMUNITY ORGANISATIONS - Selcen Oner (European Scientific Journal, ESJ, 2014)
This article analyses the role of Turkish community organisations in Germany. It first explains the historical background of Turkish immigrants in Germany, secondly the role of civil society in Germany, particularly the historical background of Turkish community organisations are analysed and lastly the types of Turkish community organisations, the interactions among each other and their role in Germany are evaluated.